Aerodynamic Optimization of an Over-the-Wing-Nacelle-Mount Configuration. (19th May 2011) - Sasaki Sasaki, Daisuke Daisuke; Nakahashi Nakahashi, Kazuhiro Kazuhiro
Abstract : An over-the-wing-nacelle-mount airplane configuration is known to prevent the noise propagation from jet engines toward ground. However, the configuration is assumed to have low aerodynamic efficiency due to the aerodynamic interference effect between a wing and a nacelle. In this paper, aerodynamic design optimization is conducted to improve aerodynamic efficiency to be equivalent to conventional under-the-wing-nacelle-mount configuration. The nacelle and wing geometry are modified to achieve high lift-to-drag ratio, and the optimal geometry is compared with a conventional configuration. Pylon shape is also modified to reduce aerodynamic interference effect. The final wing-fuselage-nacelle model is compared with the DLR F6 model to discuss the potential of Over-the-Wing-Nacelle-Mount geometry for an environmental-friendly future aircraft.